Basic Concepts in Tumor Angiogenesis (International Journal of Medical and Surgical Sciences, 2014)
The transformation of normal cells into cancer encompasses a complex series of events, such as genetic disorders, aberrant cell cycles, changes in the phenotype and in cell adhesion, inhibition of apoptosis and generation of new blood vessels. This process is controlled by factors that promote and which factors inhibit it, and the balance between these factors determines their advancement, aggressiveness and prognosis. This review shows basics in the process of tumor angiogenesis.
Keywords: Angiogenesis; Blood vessels; Endothelial cells; Cancer